Atividade biológica do extrato de moléculas de euterpe oleracea mart. (açaí) sobre biofilme de Candida parapsilosis e tropicalis - BRITO, Larissa Lira (2017)
Candidiasis occurs as a consequence of an immune disorder of the host and of the virulence factors of these yeasts. Candida albicans has been reported as the most prevalent, followed by C. parapsilosis, C. glabrata, C. tropicalis and C. krusei. The resistance of microorganisms is increasing due to the indiscriminate use of antimicrobials used in the treatment of infectious diseases. Prompted researchers to study new antimicrobial substances from various sources, including medicinal plants. This study aims to elucidate the antifungal potential of açaí on biofilms of Candida. Biofilms are designated as drug resistant growth forms representing a serious threat to immunocompromised individuals. The objective of this work was to evaluate the in vitro antifungal activity of açaí extract (Euterpe Oleracea) against biofilms formed by Candida strains. Euterpe peel and core extract has a strong effect on the formation of biofilms by both C. tropicallis and C. parapsilosis species, inhibiting its formation in different concentrations of the extracts, showing the effect of natural products, evidencing phytochemicals, Activities and potential of Euterpe for future industrial applications.